Synthesis and photopolymerization of multifunctional methacrylates derived from Bis-GMA for dental applications - Ahn, KD; Chung, CM; Kim, YH (JOHN WILEY & SONS INC, 1999)
Two multimethacrylates having three methacrylate groups (BPA-SM) and four methacrylate groups (BPA-4M) have been prepared by reacting hydroxyl groups of 2,2-bis [4-(2'-hydroxy-3'-methacryloyloxypropoxy)phenyl] propane (Bis-GMA) with methacryloyl chloride. BPA-SM and BPA-4M have much lower viscosities than the starting Bis-GMA, because they have only one or no hydroxyl group. Photopolymerizations of the multifunctional methacrylates were conducted by exposure to visible light using camphorquinone and 2-(N,N-dimethylamino)ethyl methacrylate as a photoinitiating system. High conversions >50% resulted from photopolymerization of BPA-SM, whereas Bis-GMA showed lower conversions under the same condition, implying better mechanical properties for the composite resins made from BPA-3M. BPA-4M showed much lower conversions in the photopolymerization condition. Water sorption of the photocured composite of BPA-3M containing 50 wt % of inorganic fillers was found to be 0.15%, which is only one-tenth of the commercial Bis-GMA composite. (C) 1999 John Wiley & Sons, Inc.
Keywords: REACTION BEHAVIOR; COMPOSITES